The Importance of User Experience in Context E-Commerce - Bruno F. CARVALHO; Miguel A. BRITO; João P. SILVA (Communications of International Proceedings, 2021)
In the last few decades, the “User Experience” term has been progressively inserted into the digital environment mainly in the E-commerce systems as it has a great impact on their success. In this way, the main objective of this article is to explore the term User Experience as well as to report on aspects related to it since the users of an e-commerce system want to have a good User Experience. In order to achieve this goal, it is presented how to model the user’s experience so that the user’s needs and expectations are attended to.
Keywords: User Experience; Usability; E-commerce.